Dejavniki tveganja za nastanek patelofemoralne bolečine - Manojlović Ivezić, Denisa (Šport (Ljubljana), 2022)
Patellofemoral pain (PFP) is one of the most common pain conditions in the knee area and occurs during activities that overload the patellofemoral joint. Despite the growing interest regarding PFP, the predominant risk factors for its occurrence are still not established. Very few factors associated with PFP are recognized as risk factors for its occurence. Recent evidence suggest that risk factors differ between subgroups of people with PFP. In adults, impaired knee extension strength has been found to be the primary risk factor for the occurence of PFP. Surprisingly, in adolescents, a causal relationship has been found in in case of increased hip abduction strength. It is emphasized that understanding the risk factors in different populations is a key step in the successful management of PFP. Early identification of risk factors may help to appropriately target the exercise interventions and to contribute to an effective long-term reduction of the burden caused by a chronic and recurrent condition such as PFP.
Keywords: bolečina; dejavniki tveganja; etiologija; kolenski sklep; šport